Overview of online learning environment - Mai Thanh Phương (Journal of Technical Education Science, 2013)
Nowadays, online learning has been changed significant development to help learners more opportunities for distance learning. Information and communication Technology have contributed to the evolution for forms of learning. The online learning can be exprected to become a major learning in the future. This article aims to provide a historical of online learning environment in the world and Viet Nam to serve as a theoretical basic for the design of online learning systems later.